2019
DOI: 10.1016/j.spinee.2018.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glycohemoglobin HbA1c is associated with low back pain in nonoverweight diabetics

Abstract: LBP is significantly related to DM status, but this relationship is complex and may interact with BMI. These results support the concept that LBP may be improved in normal weight diabetic subjects with improved glycemic control and weight loss, and that all obese LBP subjects may benefit from improved weight loss alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Several recent studies have investigated the effects of the clustering of MetS components on musculoskeletal disorders [6, 8], as well as on CVD or mortality [3, 4]. In addition, the associations of LBP with individual factors of MetS have been investigated, including abdominal obesity [22], hypertension [23], dyslipidemia [17], and impaired blood glucose [24]. However, none have investigated the effect of the accumulation of MetS components on LBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have investigated the effects of the clustering of MetS components on musculoskeletal disorders [6, 8], as well as on CVD or mortality [3, 4]. In addition, the associations of LBP with individual factors of MetS have been investigated, including abdominal obesity [22], hypertension [23], dyslipidemia [17], and impaired blood glucose [24]. However, none have investigated the effect of the accumulation of MetS components on LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have investigated associations between LBP and individual components of MetS such as abdominal obesity [22], hypertension [23], impaired blood glucose [24], and lipid disturbance [17], data on the relationship between LBP and MetS itself are very scarce in the population setting. Only one community-based study has described such associations [25], indicating a significant association between LBP and MetS in women only.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance was assessed using the HOMA-IR, which was calculated from fasting levels of insulin and glucose, using the formula [fasting serum insulin (μU/mL) × fasting plasma glucose (mmol/L)/22.5], analyzed as a continuous variable and further categorized based on the cutoff point of 2.5 [40]. Individuals were identified as having diabetes if their HbA 1c was ≥6.5% [41]. Chronic inflammation was measured using CRP by latex-enhanced nephelometry and analyzed as a dichotomous variable based on the cutoff point of one suggesting clinically raised CRP [42].…”
Section: Methodsmentioning
confidence: 99%
“…An association between diabetes and LBP has been indicated in some population studies 3 4. Other studies have suggested a relationship between increased blood glucose levels and LBP 5 6. It has also been suggested that lumbar spinal stenosis may be associated with diabetes mellitus 7…”
Section: Introductionmentioning
confidence: 98%